Work begins on substance : the Doha development agenda (2002)
Provides a summary of work that is currently being done with regard to the Doha Development Agenda. Presents briefly the Agenda structure; the chairpersons of negotiating groups (until the 5th Ministerial conference in September 2003); and, the main benefits to business from the WTO system.
Keywords: TRADE NEGOTIATIONS